Controlled Release of an Anti-inflammatory Drug Using an Ultrasensitive ROS-Responsive Gas-Generating Carrier for Localized Inflammation Inhibition - Chung, Ming-Fan; Chia, Wei-Tso; Wan, Wei-Lin; Lin, Yu-Jung; Sung, Hsing-Wen (Journal of the American Chemical Society, 2015)
Inflammation is associated with many diseases, in which activated inflammatory cells produce various reactive oxygen species (ROS), including H2O2. This work proposes an ultrasensitive ROS-responsive hollow microsphere (HM) carrier that contains an anti-inflammatory drug, an acid precursor consisting of ethanol and FeCl2, and sodium bicarbonate (SBC) as a bubble-generating agent. In cases of inflamed osteoarthritis, the H2O2 at low concentration diffuses through the HMs to oxidize their encapsulated ethanol in the presence of Fe2+ by the Fenton reaction, establishing an acidic milieu. In acid, SBC decomposes to form CO2 bubbles, disrupting the shell wall of the HMs and releasing the anti-inflammatory drug to the problematic site, eventually protecting against joint destruction. These results reveal that the proposed HMs may uniquely exploit biologically relevant concentrations of H2O2 and thus be used for the site-specific delivery of therapeutics in inflamed tissues.